Deciphering a molecular mechanism underlying lymphovascular invasion in breast cancer - Aljohani, Abrar (2022)
Background: Despite advancements in the early detection of breast cancer (BC) and improved access to therapeutic options, the global mortality rate due to BC among women remains high. BC progression is a complex and multistep process. Lymphovascular invasion (LVI), one of the earliest stages of metastasis in BC, is controlled by specialised molecular pathways and is strongly associated with poor outcomes. LVI signifies the expansion of tumour cells towards the peritumoural region inside lymphatic spaces and blood vessels. A successful LVI event requires the involvement of a variety of cellular, biophysical, and biochemical pathways. Because the underlying molecular mechanisms of LVI are complex and involve connections with other oncogenic and metastatic pathways, no targeted treatments are currently available to prevent the progression of LVI and metastatic recurrence. Investigation into the molecular determinants of LVI is critical in elucidating the molecular mechanisms underlying LVI, discovering novel prognostic factors, and identifying possible treatment targets for invasive BC. The genes that play a role in the pathogenesis of LVI in invasive BC have received little attention; it was therefore hypothesised that by conducting bioinformatic analyses, key genes related to LVI in BC could be identified, some of which may have prognostic value, serve as potential therapeutic targets, and have roles in the various mechanisms regulating the development of LVI. This study aimed to identify genes associated with LVI, evaluate the clinicopathological and prognostic significance of the identified genes at the mRNA and protein levels, and investigate their functional roles.